Ocrelizumab-induced colitis—critical review and case series from a Romanian cohort of MS patients - Vodă, Ileana Maria; Tiu, Vlad Eugen; Răuță, Luiza; Ciucur, Paul; Mușuroi, Andreea Ioana; Tomescu, Alina Flavia; Humă, Nicoleta Laura; Dobrițoiu, Florin; Terecoasă, Elena; Negreanu, Lucian; Tiu, Cristina (Frontiers in Neurology, 2025)
BackgroundWidespread use of ocrelizumab, an anti-CD20 monoclonal antibody, for treating patients with multiple sclerosis (MS), has led to an increase in reported adverse events following real-world observation. Among these, drug-induced colitis is a rare, but severe side effect, prompting a recent FDA statement regarding this safety concern. Objectives: We analyzed a cohort of ocrelizumab treated patients in our MS center to evaluate the incidence of drug-induced colitis.MethodsWe present a critical review of the available literature on diagnosis and management of anti-CD20 induced colitis and display a case series of 3 suspected patients in our cohort.ResultsTwo patients met the full criteria for ocrelizumab-induced colitis, while a third partially met the criteria. Following symptomatic treatment and discontinuation of ocrelizumab, the patients showed favorable outcomes.ConclusionOcrelizumab-induced colitis is a rare, but severe adverse event. Its incidence may be higher than expected, reaching 1,95% in our cohort of MS patients. Further reporting of such cases is essential to broaden our understanding of this side effect.